Socialization of Goleman's 6 Leadership Types to Prepare Young Leaders for the Future - Fitra, Aura Alviona; Yulyantika, Nadya Rindy; Romadlona, Nohan Arum; Permata, Fedina Dyah Ayu; Nastiti, Jihan Pratika; Mujiyanti, Kharisma Pingky; Nuraziizah, Nida’a Astie; Firdaus, Nur Wardatul; Almutairi, Reem Iafi (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
This leadership is the art of influencing someone, either individually or in groups. According to Daniel Goleman, leadership styles are divided into 6: Commanding, Visionary, Affiliative, Democratic, Pacesetting, and Coaching. Basically, leadership can be formed and trained since school age. This is done so that when they are faced with a problem, they can easily find several alternative solutions to the problem In order to realize a young generation that has a leader's soul, community service activities are carried out at SMP Ma'arif Kota Batu. This socialization activity aims to introduce and increase knowledge about Goleman's 6 leadership styles. The method used in socialization is using the lecture method using power point media with material on 6 types of leadership according to Goleman. To measure the level of knowledge of students, a pre test was conducted before socialization and a post test was conducted after socialization. The result is an increase in knowledge of female students after socialization so that it is expected that students can recognize their own leadership style. As for the suggestions in this activity, namely the use of leadership material to direct female students in increasing their understanding and leadership skills in an organization.